University teachers need to be researchers rather than priests of cargo cults. - Dave Thomas Burnapp (Association for Learning Development in Higher Education (ALDinHE), 2011)
The concept of cargo cults, although hotly disputed, was originally conceived to describe the results of interfacing cultures with very different technologies and methods of production. The concept has previously been used to describe in a figurative manner a distinction between science and pseudoscience, the latter being typified by not following a method of scientific integrity, including scrutiny of claims. Here the analogy is adapted to justify a claim that teachers at universities need to be actively involved in research in order to demonstrate to their students that the knowledge which is expected, accepted, and respected in universities is subject to constant debate, is often ambiguous, and is never completed.